The Mongols, their upbringing, their home, their first wars (Journal of the College of Basic Education, 2022)
The period of the Mongol invasion at the hands of Genghis Khan and his successors to the Islamic countries was initially a periodA difficult situation in which Muslims suffered killing and torture, and their country was devastated and devastated, but it soon changedThe situation gradually until the time came when the Mongols were influenced by the civilization of the conquered and converted to their religion. And they proceededThey reform what their forefathers spoiled, and they accept to contribute their share in the revival of Islamic civilization in various fieldsmanifestations.